A Voice Search Approach to Replying to SMS Messages in Automobiles - Ju, Y. C.; Paek, Tim (International Speech Communication Association, 2009)
Automotive infotainment systems now provide drivers the ability to hear incoming Short Message Service (SMS) text messages using text-to-speech. However, the question of how best to allow users to respond to these messages using speech recognition remains unsettled. In this paper, we propose a robust voice search approach to replying to SMS messages based on template matching. The templates are empirically derived from a large SMS corpus and matches are accurately retrieved using a vector space model. In evaluating SMS replies within the acoustically challenging environment of automobiles, the voice search approach consistently outperformed using just the recognition results of a statistical language model or a probabilistic context-free grammar. For SMS replies covered by our templates, the approach achieved as high as 89.7% task completion when evaluating the top five reply candidates.